Nanosilica Particulate Magnetic as Alternative Filler on Natural Rubber Composites with Human-Tissue-Like Mechanical Characteristic - Riri Murniati; Arini Fitria Gunawan; Muhammad Nuraliffudin Saputra; Imastuti Imastuti; Mikrajuddin Abdullah (Universitas Andalas, 2022)
There have been no reports of the simultaneous application of natural fillers, such as magnetite and natural zeolites, to increase the strength of composites containing silica (SiO2) fillers as reinforcing fillers in natural rubber. This study has investigated the effect of magnetically modified natural zeolite on nanosilica-reinforced natural rubber composites that include a mechanical characteristic like human tissue. We use technical specifications rubber (TSR) SIR 20 with nanosilica reinforced fillers and Titanate coupling agent (TCA) as fillers and elastomer binders. The results showed that the nanosilica-zeolite-magnetite (Fe3O4) mixture had an influence on strength and stiffness and could be a substitute filler. The precursors made with some variations include the optimization of filler and the optimization volume fraction of nanosilica. Mechanical characteristics of different human body part tissue were compared to the control samples and have similar mechanical characteristics with internal human tissue characteristic. Based on these results, nanosilica fillers combine with magnetically modified zeolites and titanate coupling agents, potentially as an alternative filler to replace carbon black, and are applicable for synthetic muscle replacement cadavers with a customized formula.